Política pública de habitação em Cuiabá : o trabalho técnico social no PHBB - Silva, Francismary de Amorim (2013)
This thesis deals with the study of work social worker, with a view participation and citizenship in municipal housing policy in the city of Cuiabá, focusing the program Inhabit Brazil Bid-PHBB. The study sought to identify how the beneficiaries were positioned opposite social participation, and what involvement in program development, obstacles and possibilities of increasing social participation, through the figure of the State, and the strengthening of citizenship of beneficiaries the program. To carry out these surveys were conducted literature searches, analysis of institutional documents and semi-structured interviews, which were subject to the locals, originating beneficiaries of the program studied. The survey results indicate that beneficiaries were positioned so little participation on the work done and had little decision-making power. Based on these results it is possible to point out the possibilities of increasing social participation in housing policy, through the figure of the State, must be understood as a regular exercise in public policy, the beneficiary no longer conceived only as agent receiver, but how effective transformer social. The strengthening of citizenship is still under construction, being a challenge to Cuiaba and across the country. With this, the research reveals that it is essential to establish practical measures to encourage people to social participation effectively, which is the path to citizenship.